Clinical profile of congenital heart diseases detected in a tertiary hospital in China: a retrospective analysis - Song, Linhong; Wang, Yi; Wang, Hui; Wang, Gang; Ma, Ning; Meng, Qiang; Zhu, Kunao; Hu, Siqi; Zhou, Gengxu; Feng, Zhichun (Frontiers in Cardiovascular Medicine, 2023)
Background Congenital heart diseases (CHDs) are conditions that involve structural problems to the heart's structure existing at birth, with an incidence of approximately 8 per 1,000 live births globally. CHD is one of the leading causes of maternal, fetal, and neonatal morbidity and mortality worldwide. The present study sought to examine the clinical profiles of CHD patients and provide important implications for therapeutic interventions. Methods This was a retrospective, observational, cohort study. The medical records of all CHDs patients aged between 0 and 18 years were collected from July 1, 2021 to June 30, 2022. Clinical profiles and demographic data were collected from cardiology and pediatric department registers for analysis. Results Of the 265 children with CHDs, 201 were diagnosed with acyanotic CHD (ACHD), while 64 children had cyanotic CHD (CCHD). Based on the eleventh revision of the International Classification of Diseases (ICD-11), “congenital anomaly of a ventricle or the ventricular septum” was the most common CHD. The most common symptom was failure to thrive, accounting for 18.5% of all CHD cases. The most frequent symptom in ACHD was murmur (93.53%) and sweating (80.60%), whereas the most common symptom in CCHD was sweating (95.31%) and cyanosis (84.38%). Conclusions This study retrospectively analyzed CHD clinical characteristics from children receiving care at the seventh center, which forms a proper basis for appropriate clinical treatments and further studies.